Dendritic cell expression of CD24 contributes to optimal priming of T lymphocytes in lymph nodes - Zhang, Xuejun; Yu, Chuan; Liu, Jin-Qing; Bai, Xue-Feng (Frontiers in Immunology, 2023)
CD24 is a GPI anchored cell surface glycoprotein whose function as a co-stimulatory molecule has been implicated. However, the function of CD24 on antigen presenting cells during T cell responses is not well understood. Here we show that in the CD24-deficient host, adoptively transferred CD4+ T cells undergo inefficient expansion and have accelerated cell death in lymph nodes, which results in insufficient priming of T cells. Insufficient expansion of T cells in the CD24-deficient host was not due to depletion by host NK, T and B lymphocytes. Transgenic expression of CD24 on DC restored T cell proliferation and survival in CD24-/- mice. Taken together, we have found that DC expression of CD24 has a significant effect on T cell priming in lymph nodes.